Efficacy of recreational hunters and marksmen for host culling to combat chronic wasting disease in reindeer - Atle Mysterud; Olav Strand; Christer M. Rolandsen (Wildlife Society Bulletin)
ABSTRACT Most populations of large mammals in developed countries are managed by human hunting, but there are surprisingly few empirical studies about the benefits and limitations of using recreational hunters to achieve specific management objectives. In particular, the extensive host culling required to markedly reduce population densities to combat some wildlife diseases may conflict with the management aims of landowners and hunters. This is particularly acute in the case of chronic wasting disease (CWD) in cervids, which has now emerged in reindeer (Rangifer tarandus) in Norway. We analyzed the relative efficacy of approximately 1,000 recreational hunters and 30 professional marksmen during the eradication of the entire CWD‐infected population of >2,000 reindeer in Norway. The government changed a series of legislation that would normally limit the efficacy of recreational hunters; these changes were linked to the duration of the hunting season, the specificity and size of the quotas, and spatial access rights. Efforts were taken to reduce both the searching time (hunters were given information on herd whereabouts) and handling time (helicopter aid for transport) of the recreational hunters. We compared 1) recreational hunting under ordinary legislation (up to 2016), 2) recreational hunting with less legislation (2017), and 3) culling by marksmen that were allowed to use both snowmobile and helicopter. Despite all of the changes in legislation, harvest by recreational hunters only increased from 241–316 during 2014–2016 to 582 reindeer in 2017 and was below management targets, while marksmen culled 1,399 reindeer, with a daily average and maximum offtake well above that of the hunters. The hunters shot more animals in the early season and during weekends. Offtake by both the hunters and marksmen were equally negatively affected by fog, which reduced visibility. We discuss the relative merits of using hunters and marksmen for wildlife control in general and limits to how legislation can increase offtake. We highlight the need for more research into how the use of marksmen comes with a cost in terms of social conflict. © 2019 The Authors. Wildlife Society Bulletin published by Wiley Periodicals, Inc. on behalf of The Wildlife Society.